Immunohistochemical expression and prognostic significance of DCC (deleted in colon cancer), p53 protein and proliferative marker Ki-67 in colorectal colon cancer. - Yashar, Genghis; Basheska, Neli; Prodanova, Irina; Kubelka-Sabit, Katerina; Dimovski, Aleksandar; Stefanovska, Ana-Marija; Zografski, George (Springer, 2005)
Objectives: The objective of this study was to evaluate the immunohistochemical expression of Deleted in colon cancer (DCC), p53 protein and proliferating index Ki-67 in correlation with various clinico-pathological (age, sex, tumor status, lymph node involvement, localization, tumor diameter, grade of differentiation, histological type) and biomolecular parameters (loss of heterozygosity of the long arm of chromosome 18 and microsatellite instability) in colorectal cancer patients. In addition, the prognostic significance of their influence on overall survival (OS) was also estimated. Methods: A retrospective analysis of 100 patients with colorectal cancer who underwent large bowel resection with regional lymphadenectomy was conducted in the period between 1995 and 2000. All the patients were in stage II and stage III of the disease according to the postoperative TNM classification of UICC (1997) guidelines. The immunohistochemical expression of protein products of the DCC, p53 tumor suppressor genes and Ki-67 proliferating index were semi-quantitatively evaluated. Biomolecular analyses for the loss of heterozygosity of the chromosome 18q and microsatellite instability were performed with the Polymerase chain reaction (PCR) technique. Results: In our case series, 57 (57%) patients were in stage II, and the remaining 43 (43%) patients in stage III of the disease. During the follow-up period (mean 53, range 5-97 months), 41(41%) patients died of the disease. The expected 5-year OS rate was 58.6%. In the univariate analysis, tumor status, lymph node involvement, sex, age, tumor grade, p53 protein expression and Ki-67 proliferating index were parameters with prognostic significance related to OS (p<0.05). Among these variables, in the multivariate analysis the tumor status and Ki-67 proliferating index were selected as independent and significant prognostic factors related to OS (p=0.0019). According to the value of the prognostic index (PI) defined by Cox regression model, the patients were categorized in two distinct risk groups. The 5-year OS rate of the low- and high-risk group patients was 65.0% vs. 29.4% (p=0.001). The 5-year OS for stage II was 71.1% vs. 40.0% (p=0.05) and for stage III of the disease it was 54.8% vs. 25.0% (p=0.03), respectively. Conclusions: These data indicate that defining prognostic groups in each stage of the disease allow an exact and objective selection of colorectal cancer patients with different death risk. Therefore, the prognostic index (PI) as an indicator of the patient’s place in the prognostic spectrum could be a sound basis for an appropriate planning.
Keywords: colon cancer; immunohistochemistry; Deleted in colon cancer (DCC); p53; Ki-67; Polymerase chain reaction (PCR); prognosis; overall survival; prognostic group